Application of Bacterial Nano Cellulose as a Reinforcing Material in The Liner Test Paper (Universitas Negeri Semarang, 2020)
This research is about the application of Bacterial nano cellulose (BNC) as a reinforcing material in the making of liner test paper. BNC was obtained from the fermentation of banana peel extract using Gluconacetobacter xylinum bacteria obtained from the making starter of nata de coco. The reason for using banana peel waste is because it’s available in large number all across Indonesia. BNC is mixed with secondary fiber as a raw material for making liner test paper. From the experimental handsheets results, strength properties and absorption properties were then tested. Variations in the composition of the use of BNC are 0% (blank), 5%, 10%, 15%, 20%, 25%, 30% of the handsheet dry weight. The BNC is also applicated on surface sizing as a substitute for the surface sizing agent. The results of this study indicate that BNC can be used as an alternative raw material on wet end and on surface sizing, because both applications can increase the strength properties of liner test paper, and can reduce the use of chemical additive. The highest increase in strength properties of liner test paper was obtained at the composition of nano cellulose 30% and using surface sizing. Ring crush index is 14.02 Nm / g, concora index is 12.73 Nm / g, bursting index is 3.78 KPa.m² / g, ply bonding is 388.57 J / m². The absorption properties of paper increases but it has a low prosity. The highest cobb size results are obtained at 30% BNC composition, which is 45.30 g / m2 without using surface sizing and 41.83 g / m² using surface sizing. The highest porosity value is obtained at 30% BNC composition, which is 158 s / 100cc using surface sizing. This research is expected to be a reference for further research in the field of BNC, as the alternative raw materials besides wood in paper making.